FACTORS AFFECTING STUDENT REGISTRATION IN THE MBKM PROGRAM OVERSEAS STUDENT EXCHANGE - Fatimah Sari Siregar; Muhammad Shareza Hafiz; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to Test the Factors That Affect Student Participants in Participating in the MBKM Overseas Student Exchange Program, the variables to be tested are language readiness, intellectual, emotional and spiritual skills towards student participants in the MBKM program for foreign student exchange. Where at this time, Indonesia continues to innovate in the world of education, in order to get human resources that are forgiven, and have international competitiveness. Therefore, it is necessary to know the variables that can affect student interest in participating in the MBKM program, especially in overseas student exchanges. The analytical tool used in the study was SmartPLS, as for the results obtained that there was a significant influence of language readiness on student participation in the MBKM program. There is a significant influence of intellectual skills on student participation in the MBKM program. There is a significant emotional influence on student participation in the MBKM program.